Rancang Bangun ROV (Remotely Operated Vechile) Untuk Mengukur Kedalaman Air Berbasis Sensor MS5803-14BA - Marzuarman, Marzuarman; Faizi, M. Nur; Stephan, Stephan (Faculty of Engineering, Universitas Tanjungpura, 2020)
Water is an important compound for all forms of life on earth. The depth of water is closely related to productivity, vertical temperature, light penetration, density, oxygen, and nutrients. The depth of water affects biota which are cultivated. It is related to the pressure received in the water, because the pressure increases as the depth increases. This research makes Remotely Operated Vechile (ROV) to measure water depth using MS5803-14BA pressure sensor, joystick controller and eqipped with Arduino Mega as the control of the ROV. The ROV is also equipped with a camera to monitor the underwater condition. In this research, the ROV is designed to ease people in measuring the depth of water without diving. The ROV is designed to produce good measurements at depths above 1 meter, with error values of 0.3% to 2.1%. Therefore, ROV can be applied as a measurement media of the water depth. Moreover, the camera on the ROV is able to monitor underwater condition which gives good image results in clear water condition. Therefore, it is useful to search objects in the ocean.